The Role of Partnerships in the Internationalisation Process of Small Knowledge Intensive Firms (SKIFs) - Zucchella, Antonella; Kabbara, Diala (Management international / International Management / Gestiòn Internacional, 2013)
There is important evidence that Small Knowledge Intensive Firms (SKIFs) have demonstrated some unique characteristics in their internationalisation process. The process takes place earlier in the life of the firm and develops due to the role played by partnerships. The paper analyzes three different SKIFs through a cross case study method. We build on different process based models that have studied the internationalisation process of international ventures. The findings show that the SKIFs internationalisation consists of a series of phases characterised by triggering factors. The paper sheds new light into which type of partnerships mostly matter in the growth of SKIFs.